Estudio de prefactibilidad para la instalación de una planta procesadora de un alimento tipo hamburguesa de quinua (Chenopodium quinoa) - Cajahuaringa Olivares, Lesslie Yomira (2020)
The objective of this study is to determine the market, technology, economic, financial and social viability of the installation of a quinoa burger-type food processing plant. Burgers of 10 cm in diameter will be produced, the target market will be Metropolitan Lima, since it is the place where the largest number of supermarkets is located, which will be the main customers. The established sales values are S / 14,00 the box of four units. The production plant will be located in the district of Villa El Salvador, in the Lima region. The plant size is 103,29 tons of finished product. This result comes in relation to size-market, since it is the limiting factor, in terms of required technology it is feasible to acquire and use it within the country. Regarding the investment, the total assets of the company are S / 726 471,30 and the working capital is S / 247 014,28, so there is a total investment of S / 973 485,58. In addition, 60% financing of the investment with a 6-year horizon without grace period and at an effective annual rate of 14,99% was considered. Regarding the economic evaluation, it yields S / 381 299,73 of net present value, 43,70% of internal rate of return, in benefit-cost ratio is 1,39 and a recovery period of 2 years and 3 months with 7 days. Meanwhile, the financial evaluation is S / 620 228,09 net present value, 84,26% internal rate of return, with respect to the B / C ratio 2,59 and a recovery period of 1 year, 2 months and 5 days.